Bioquímica e citogenética de jundias (Rhamdia quelen) expostos a diferentes concentrações de tório - Correa, Lizelia Moraes (2007)
The objective of this study was to evaluate the effect of thorium (Th) on the metabolism of silver catfish (Rhamdia quelen) through biochemical parameters from the muscle tissue (glycogen, glucose, lactate, protein and ammonia), lipidic peroxidation levels (TBARS), catalase (CAT) and glutathione-S-transferase (GST) in the hepatic and muscular tissues and cytogenetic parameters through the evaluation of nuclear abnormalities in blood cells. Silver catfish juveniles (8.78 ± 0.10cm; 6.41 ± 0.17g) were exposed to different waterborne concentrations of ²³²Th (in μg.L-1): 33.6±8.7; 106.5±37.1; 191.6±19.0 and 758.4±150.4 for 15 days. The levels of muscle glycogen were significantly reduced in fish exposed to 106.5 μg.L-¹ Th, while glucose and protein increased in those exposed to 758.4 μg.L-¹ Th. Lactate levels were higher in fish maintained at 191.6 μg. L-¹ Th and ammonia was higher in those exposed to 33.6, 106.5 and 191.6 μg.L-¹ Th. The lipidic peroxidation levels were diminished in the liver of silver catfish exposed to all tested concentrations of Th. In the muscle lipidic peroxidation was higher in juveniles maintained at 106.5 μg.L-¹ Th and lower in those exposed to 191.6 and 758.4 μg.L-¹ Th. The CAT activity was higher in the hepatic tissue (but not muscle) of fish exposed to all tested concentrations of Th. The GST activity in the liver was lower in fish exposed to 33.6 and 106.5 μg.L-¹ Th, and in the muscular tissue of those maintained at 758.4 μg.L-1 Th. Silver catfish exposed to 106.5 μg.L-¹ presented a significant induction of micronuclei, but no alterations in other erythrocyte abnormalities were observed. These results suggest that exposure to waterborne Th induces changes in the metabolic state, increase of lipidic peroxidation in the liver, some alterations of CAT and GST, and DNA damage.